Vibration Prediction Model for Building Developments Adjacent to Railways - Seiner, Martin; Pistone, Elisabetta; Achs, Gunther; Toll, Hanno (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
This paper presents the experimental and computational evaluation of ground-borne noise and vibration impacts at sensitive receivers in the vicinity of existing track sections. Vibration problems occur as an effect of train passings adjacent to buildings and structures, thus needing to satisfy stringent vibration and ground-borne noise criteria. Therefore, it is necessary to quantify comprehensively the vibration impact in the design of new developments and the compliance with the provided criteria. Test measurements of vibration propagation through the structure are often possible only under certain circumstances since, based on the construction work progress, many relevant parts of the analyzed structure have not yet been completed. In such cases, measurement data is combined with computation data applying the Finite-Element-Method (FEM). The structure is modelled as a basis for dynamic analyses and the subsequent tuning of damping systems. The paper presents a semi-empirical prediction model on the basis of measurements and computational models that was applied to international projects. One of the projects is in close vicinity of one of the metro stations in Doha, including a sixlevel underground parking structure with various facilities and a large development with numerous towers of different use on top. Another project that will be presented in the paper is a luxury hotel located adjacent to another station along one of the Doha metro lines. Outcomes summarize the state of the art aforementioned topic.